PERAN ORANG TUA DALAM MENDUKUNG PENDIDIKAN INKLUSIF: STUDI LITERATUR BERBASIS TEORI DAN PRAKTIK - Ismail; Wardaliyanti; Nurlaila; Muhammad kadir; Nurul islamiah; R. Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education is an approach that ensures equal learning opportunities for all students, including those with special needs, within the same educational environment. Parents play a crucial role in supporting the successful implementation of inclusive education through emotional, social, and academic support. This study aims to examine the role of parents in supporting inclusive education through a literature review based on theoretical perspectives and practical findings. The method used is a library research approach by analyzing relevant journals, books, and previous studies. The results indicate that parents act as learning facilitators, advocates for their children, and active partners with schools in the educational process. Furthermore, effective communication and collaboration between parents and teachers significantly contribute to children’s optimal development. However, challenges such as limited parental understanding of inclusive education and resource constraints are still evident. Therefore, strong collaboration among schools, families, and policymakers is essential to provide continuous support and education for parents.